Global disease burden of colorectal cancer attributable to high BMI has more than doubled over the past 30 years - Zeng, Jiamin; Li, Wenjie; Wu, Zhiming (Frontiers in Oncology, 2025)
BackgroundColorectal cancer (CRC) significantly contributes to global cancer-related mortality and morbidity, with a high body mass index (BMI) being a key modifiable risk factor. Understanding the evolving burden of CRC attributable to high BMI is essential for informing public health strategies and meeting global noncommunicable disease targets.MethodsUsing data from the Global Burden of Disease Study 2021, we examined the age-, sex-, and location-specific CRC burden attributable to obesity. Trends in age-standardized death rates (ASDR) and disability-adjusted life-years (DALYs) were assessed using the estimated annual percentage change (EAPC).ResultsBetween 1990 and 2021, CRC deaths attributable to obesity increased from 41,535.8 (95% UI 17,665.6–67,379) to 99,268.0 (95% UI 42,956.3–157,948.8), while DALYs increased from 15,042.1 (95% UI 4,297.8–16,319.7) to 64,664.2 (95% UI 102,159.3–375,234.0). High-SDI regions showed declining ASDR (EAPC = −0.64, 95% UI −0.69 to −0.59) and DALY rates (EAPC = −0.48, 95% UI −0.52 to −0.43) but retained the highest absolute burden. In contrast, the middle- and low-SDI regions exhibited alarming increases in both ASDR and DALY rates, with EAPCs exceeding 2.0. East Asia reported the highest absolute mortality and DALY burden, whereas Australasia showed the lowest burden and declining trends. Inequality in the CRC burden widened substantially between the high- and low-SDI regions during the study period.ConclusionThe global burden of CRC attributable to high BMI doubled from 1990 to 2021, with increasing disparities across SDI regions, especially in the low- and middle-SDI areas. Urgent strategies focusing on obesity prevention, early detection, and equitable care are essential to reduce this burden and achieve Sustainable Development Goals by 2030.